The interrelation of needs and quality of life in first-episode schizophrenia. - Landolt, K; Rössler, W; Burns, T; Ajdacic-Gross, V; Galderisi, S; Libiger, J; Naber, D; Derks, E; Kahn, R; Fleischhacker, W (2012)
The interrelation between needs for care and quality of life has been described and replicated by several studies. The present work aims to add to the understanding of longitudinal interrelations between needs for care, quality of life, and other outcome measures by analyzing a sample of patients at the onset of schizophrenia. This study relied on data from the EUFEST trial, designed to compare first- and second-generation antipsychotics during 1 year. At baseline, 498 patients have been included. The first (baseline) and the last assessment (12 months after baseline) were used for the analyses. Predictors of quality of life were determined using regression analyses. We tested the complex longitudinal interrelations between baseline and outcome measures with structural equation models. Unmet needs were not definitively confirmed as a predictor of subsequent quality of life, unless unmet needs changing to no needs were separated from unmet needs changing to met needs. Each unmet need that changed to no need enhanced the quality of life (mean score 1-7) by 0.136 scale points. This study suggests that when studying quality of life and needs for treatment, it is crucial to differentiate whether unmet needs disappeared or whether they were met, as the former has a stronger impact on quality of life.